Trieste and the meaning of nowhere - Morris, Jan 1926-2020 (Simon & Schuster, 2001)
The author tells the story of the Italian city of Trieste which has come to represent her own life.
Map on lining papers.
Keywords: Morris, Jan <1926-> -- Travel -- Italy -- Trieste; Geschichte; Italien; Trieste (Italy) -- Description and travel; Triest